2007
DOI: 10.1007/s10661-007-9695-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead, cadmium and copper in roadside soil and plants in Elazig, Turkey

Abstract: The concentrations of lead, cadmium and copper in roadside soil and plants in Elazig, Turkey were investigated. Soil samples were collected at distances of 0, 25 and 50 m from the roadside. The concentrations of lead, cadmium and copper were measured by Flame Atomic Absorption Spectrophotometry (FAAS). A slotted tube atom trap (STAT) was used to increase the sensitivity of lead and cadmium in FAAS. Lead concentrations in soil samples varied from 1.3 to 45 mg kg(-1) while mean lead levels in plants ranged from1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 32 publications
8
69
3
3
Order By: Relevance
“…Yet in the 1970s, Lagerwerff and Specht (1970) found that concentration of Cd, Ni, Pb, and Zn in roadside soil and grass samples from several locations decreased with distance from traffic and with depth in the soil profile. Similar results were more recently obtained by Naszradi et al (2004) and Bakirdere and Yaman (2008). Furthermore, the presence of buildings and trees as barriers for the pollutants was found to remarkably reduce road-induced pollution in the nearby gardens (Säumel et al 2012).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Yet in the 1970s, Lagerwerff and Specht (1970) found that concentration of Cd, Ni, Pb, and Zn in roadside soil and grass samples from several locations decreased with distance from traffic and with depth in the soil profile. Similar results were more recently obtained by Naszradi et al (2004) and Bakirdere and Yaman (2008). Furthermore, the presence of buildings and trees as barriers for the pollutants was found to remarkably reduce road-induced pollution in the nearby gardens (Säumel et al 2012).…”
Section: Introductionsupporting
confidence: 86%
“…A weak point of previous research is the absence of appropriate control when comparing urban to rural horticultural production. Most of the available cases addressed contaminations in urban (Bakirdere and Yaman 2008;Bretzel and Calderisi 2006;Khan et al 2008;Vittori et al 2009) or rural (Peris et al 2007) cases only. On the other hand, when a comparison of urban versus rural horticultural good is claimed (Säumel et al 2012), no reference to the growing conditions and provenance of the rural product is given.…”
Section: Introductionmentioning
confidence: 99%
“…We found in this study that the height of the road bed was significantly related to the PN value (Table 7); it is possible that a high road bed contributes to a wider range of enrichment of traffic-related metals with the same kinetic energy. The wind speed can also account for differences in the PN value at different sampling sites (Table 7; Bakirdere and Yaman, 2008). The highest road bed and strongest winds at site TTH may therefore explain the greatest enrichment in traffic-related metals in roadside soils.…”
Section: Tablementioning
confidence: 99%
“…Cu is an essential element that became toxic to both humans and animals when its concentration exceeds the safe limits. [15] The current studies [10,[15][16][17][18] showed that anti-knock agents used in automotive fuel [17,18] could contaminate the air and soils by their toxic emissions containing Pb, Cd, Zn, Ni. Also the worn out tyres, the oils leakage, the corrosion of batteries and metallic parts such as radiators increased the accumulation of these metals in roadside soil [19,20] Herein we presented a study concerning the concentrations Cd, Cu, Ni, Pb, Zn and As in soils along the Sun Highway in Romania which connects Bucharest to Constanta.…”
Section: Introductionmentioning
confidence: 99%